Bagnards, « arabes » et porte-clefs en Guyane : Naissance et usages d’un rôle pénal et colonial (1869-1938) - Marine Coquet (L’Année du Maghreb)
Far from constituting a homogeneous category, the entity of the “convict” is fragmented according to administrative categorizations which organize social relations inside and outside camp walls. One such category, based on “race,” remains understudied. Depending on the year, between 20% and 60% of convicts transported to French Guiana were from France’s North African colonies and categorized as “Arabs.” Statistics recorded for organizational purposes by the penal administration make possible a study of “Arabs” in French Guiana. Cross-checked with publications from the period and administrative correspondence between penitentiary and Colonial Office, these figures put into perspective the effects of penal typologies on relations among the transported convicts. In contemporary writings by convicts, journalists or doctors, the “Arabs” appear especially when they assumed a role assisting prison guards. The punitive configuration of “convict,” “Arab”, and porte-clefs structured a unique situation that seems, a priori, to undermine the hierarchy of “races” commonly accepted in France. Through the figure of the “Arab” convict and the porte-clefs, this contribution interrogates the social organization of Guyanese bagnards.